2012
DOI: 10.1097/mnm.0b013e32834d3c13
|View full text |Cite
|
Sign up to set email alerts
|

Timing and optimized acquisition parameters for the whole-body imaging of 177Lu-EDTMP toward performing bone pain palliation treatment

Abstract: ¹⁷⁷Lu-EDTMP can provide fine whole-body images with the best results when applying medium-energy collimation and collecting the 208 keV energy photons and alternatively by collecting both 208 and 113 keV photons for higher count statistics. The most appropriate time point for imaging is around 24 h after injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…[ 18 ] Another human study suggested 29.4 ± 12.5 MBq/kg for imaging purpose. [ 19 ] Hence, slow intravenous injection of 29.6 MBq/kg was selected for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] Another human study suggested 29.4 ± 12.5 MBq/kg for imaging purpose. [ 19 ] Hence, slow intravenous injection of 29.6 MBq/kg was selected for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Whole body scan was also performed 24, 72 h and also 7 days after the injection using single photon emission computed tomography/computed tomography infinia hawkeye4 GE gamma camera with low-energy high-resolution collimator at 108 keV peak gamma energy and windows of 15%. [ 19 ] Flare phenomenon was considered for intensifying bone pain after the injection of the drug. At this time, the patients were asked about flare phenomenon and the data were recorded including the start time of the flare phenomenon and its long-time.…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo applications of key 177 Lu radiopharmaceuticals for a variety of therapeutic procedures include peptide receptor radionuclide therapy [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], bone pain palliation [27][28][29][30][31][32][33], radiation synovectomy [34][35][36][37][38][39] and radioimmonutherapy [40][41][42][43][44][45][46]. There is a steadily expanding list of 177 Lu-labeled radiopharmaceuticals that is currently being evaluated at the preclinical research or at product development stages; these may potentially be used in vivo in humans for evaluation for radionuclide therapy [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…To recapitulate, [ 177 Lu]lutetium may be more available considering the established use in radionuclide therapy for neuroendocrine tumors and prostate cancers. Also, the features of relatively inexpensive [ 177 Lu]lutetium, such as favorable half-life, production in high-specific activity, efficient therapeutic β¯-particles, longer effect with a single administration, lower radiation of bone marrow and sufficient γ-photons for imaging make it an interesting radioisotope in bone-pain palliation therapy [ 32 , 33 , 34 , 109 , 110 ]. The impact of [ 177 Lu]Lu-phosphonate complexes in increasing survival indices is not addressed, fairly.…”
Section: [177 Lu]lutetium-ethylene Diamine Tetramethylene Phosphomentioning
confidence: 99%